Heavy social media use and psychological distress among adolescents: the moderating role of sex, age, and parental support - Mougharbel, Fatima; Chaput, Jean-Philippe; Sampasa-Kanyinga, Hugues; Hamilton, Hayley A.; Colman, Ian; Leatherdale, Scott T.; Goldfield, Gary S. (Frontiers in Public Health, 2023)
Background Despite increasing evidence that social media use is associated with adolescents’ mental well-being, little is known about the role of various factors in modifying the effect of this association during adolescence. This study examined the association between social media use and psychological distress among adolescents and explored whether sex, age, and parental support moderate this association. Methods Data came from a representative sample of middle and high school students in Ontario, Canada. Cross-sectional analyses included 6,822 students derived from the 2019 Ontario Student Drug Use and Health Survey. Results Our results showed that 48% of adolescents used social media for 3 h or more per day, and 43.7% had moderate to severe psychological distress, with a higher prevalence among females (54%) than males (31%). After adjustment for relevant covariates, heavy social media use (≥3 h/day) was associated with increased odds of severe psychological distress [odds ratio (OR): 2.01; 95% confidence interval (CI):1.59–2.55]. The association of social media use with psychological distress was modified by age (p < 0.05) but not sex or parental support. The association was stronger among younger adolescents. Conclusion Heavy social media use is associated with higher levels of psychological distress, with younger adolescents being the most vulnerable. Longitudinal studies are recommended for future research to examine in more depth the role of sex, age, and parental support in the association between social media use and psychological distress to better determine the strength and of the association.